Determinants of oral health-related quality of life in orthodontic aligner wearers: A cross-sectional analysis - Gabriela Luiza Nunes Souza; José Alcides Almeida de Arruda; Pâmella de Moura Dario; Esdras de Campos França; Marcelo de Araújo Lombardi; Giselle Cabral da Costa; Najara Barbosa Rocha; Lucas Guimarães Abreu (PLoS ONE, 2025)
Oral health-related quality of life (OHRQoL) is a critical measure for assessing the impact of orthodontic treatments, including aligners. This study aimed to investigate factors associated with OHRQoL among orthodontic aligner wearers. This cross-sectional study included 34 participants. OHRQoL was evaluated using the Oral Health Impact Profile (OHIP-14), and malocclusion severity was measure with the Dental Aesthetic Index (DAI). Data on sex, age, family income, and treatment duration were collected. Bivariate analyses were conducted to examine associations between independent variables and OHRQoL. Effect sizes (ES) were calculated to indicate the magnitude of associations, categorized as small, moderate, or large. Poisson regression was performed to identify factors associated with OHRQoL, reporting beta coefficients (Coef.) and standard errors (SE). Statistical significance was set at p < 0.05. The mean age of participants was 33.8 years. In the psychological discomfort subscale, males reported higher scores, with a moderate ES. Family income showed moderate-to-large ES, with individuals from families earning < 5 wages reporting higher scores. Higher DAI scores were significantly associated with poorer OHRQoL across the following subscales: functional limitation (p = 0.002), physical pain (p = 0.001), physical disability (p = 0.005), psychological disability (p = 0.003), social disability (p = 0.001), handicap (p = 0.037), and the total score (p = 0.001). Younger individuals also reported significantly higher scores on the handicap subscale (p = 0.007). Younger individuals and those with more severe malocclusion experienced poorer OHRQoL during treatment with orthodontic aligners. Sex and family income also significantly influenced OHRQoL outcomes.